Revisiting the School-Based Management Recent Studies - Kyaw Zay Ya; Muhammad Giatman; Fahmi Rizal; Rizky Ema Wulansari (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This paper aims at reviewing the School-Based Management recent studies. As the research method, researcher follows the systematic procedures for literature review article such as collecting data, reviewing, categorizing, and presentation. This paper answers the three questions: (A) definition of SBM, (B) factors considered to implement SBM, and (C) the roles of practitioners. Data is based mainly on secondary data, published papers in the international journals in particular. In the findings, the researcher presents a certain definition of SBM defined by prior researchers, authority sharing, facility and infrastructure management, budget management, autonomy, transparency as well as the roles of school players, in-depth and breadth. Eventually, the recommendations are also appointed for further studies to promote the School-Based Management literature.